2021
DOI: 10.1002/adsc.202100853
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Oxygen‐Mediated Radical Cyclization of Acrylamides with Boronic Acids

Abstract: A radical alkylarylation of 2‐aryl‐N‐methacryloyl indoles via autoxidation of alkylboronic acids was developed under metal‐free conditions for the construction of indolo[2,1‐a]isoquinolinone derivatives. Primary and secondary alkyl boronic acids were utilized as suitable alkyl sources with O2 as the clean and green oxidant in a simple operate mode. Moreover, this protocol can also be applied to the construction of benzimidazo‐[2,1‐a]isoquinolinone derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Combining experimental results and reported literature studies, 3,4,19–21 a possible mechanism was proposed, as shown in Scheme 4. Firstly, the Ir III photocatalyst could be excited by visible light irradiation to obtain Ir III* species, 19 h which then reduced 2a , genarating intermediate A and the Ir IV species via a single-electron-transfer (SET) process.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Combining experimental results and reported literature studies, 3,4,19–21 a possible mechanism was proposed, as shown in Scheme 4. Firstly, the Ir III photocatalyst could be excited by visible light irradiation to obtain Ir III* species, 19 h which then reduced 2a , genarating intermediate A and the Ir IV species via a single-electron-transfer (SET) process.…”
Section: Introductionmentioning
confidence: 78%
“…Over the past few years, radical initiated cascade cyclization of N -methacryloyl-substituted 2-arylbenzoimidazoles or 2-arylindoles derivatives has provided an alternative effective and powerful protocol for constructing polycyclic compounds (Scheme 1). 4 The silver/K 2 S 2 O 8 system is one such classical and effective strategy. 5 For example, Cristina Nevado and co-workers developed silver-catalyzed radical reaction cascades of N -(arylsulfonyl)-acrylamides with K 2 S 2 O 8 as the oxidant in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Under heating conditions, DTBP produced the tert ‐butoxy radical, which abstracted hydrogen from 2 or 4 to obtain C ‐centered radical [12a–b] . Following that, the addition of C ‐centered radical to the C=C bond of 1 a delivered intermediate A , which produced the aryl radical intermediate B via intramolecular radical cyclization [4d–f,12c–d] . Then, B was oxidized to produce cation C , which underwent rapid deprotonation to give the final product 3 or 5 [4d–f,12c–d] …”
Section: Methodsmentioning
confidence: 99%
“…1 So far, a large number of studies have been carried out on the synthesis of isoquinolinones. 2 The intermolecular cyclization of amides catalyzed by transition metals is one of the powerful strategies which usually needs a directing group. 3 Consequently, the development of efficient and facile methods for the synthesis of isoquinolinones still has great practical value.…”
Section: Introductionmentioning
confidence: 99%